The Kent State coverup - Kelner, J. (New York Harper and Row, Publishers., 1968)
In between the account of the trial and appeal we follow the events of May 4, 1970, through the memories of each of the living victims and their families; we trace thie lives since the shooting, share their frustratin as they try one avenue after another to get at the truth.
Keywords: Politics